Association of chronic wasting disease susceptibility with prion protein variation in white-tailed deer (Odocoileus virginianus). Issue 1 (1st January 2020) - Ishida, Yasuko; Tian, Ting; Brandt, Adam L.; Kelly, Amy C.; Shelton, Paul; Roca, Alfred L.; Novakofski, Jan; Mateus-Pinilla, Nohra E.
ABSTRACT: Chronic wasting disease (CWD) is caused by prions, infectious proteinaceous particles, PrP CWD . We sequenced the PRNP gene of 2, 899 white-tailed deer (WTD) from Illinois and southern Wisconsin, finding 38 haplotypes. Haplotypes A, B, D, E, G and 10 others encoded Q95 G96 S100 N103 A123 Q226, designated 'PrP variant A.' Haplotype C and five other haplotypes encoded PrP 'variant C' (Q95 S96 S100 N103 A123 Q226 ). Haplotype F and three other haplotypes encoded PrP 'variant F' (H95 G96 S100 N103 A123 Q226 ). The association of CWD with encoded PrP variants was examined in 2, 537 tested WTD from counties with CWD. Relative to PrP variant A, CWD susceptibility was lower in deer with PrP variant C ( OR = 0.26, p < 0.001), and even lower in deer with PrP variant F ( OR = 0.10, p < 0.0001). Susceptibility to CWD was highest in deer with both chromosomes encoding PrP variant A, lower with one copy encoding PrP variant A ( OR = 0.25, p < 0.0001) and lowest in deer without PrP variant A ( OR = 0.07, p < 0.0001). There appeared to be incomplete dominance for haplotypes encoding PrP variant C in reducing CWD susceptibility. Deer with both chromosomes encoding PrP variant F (FF) or one encoding PrP variant C and the other F (CF) were all CWD negative. Our results suggest that an increased population frequency of PrP variants C or F and a reduced frequency of PrP variant A may reduce the risk of CWD infection. Understanding the population and geographic distribution of PRNP polymorphisms may be a useful tool in CWD management.